1977
DOI: 10.1159/000155808
|View full text |Cite
|
Sign up to set email alerts
|

Nest and Home

Abstract: A nest as a rather loose construction of plant material, as it is used by most birds and some of the lowest primates, never serves as a goal of flight, very rarely as a sleeping place but mainly as a support for the offspring. A home, however, as used by many non-primate mammals and other vertebrates, is a solid construction or an excavation in a solid material (tree hole, burrow, etc.) which serves principally as a goal of flight in case of danger, also as a sleeping place and temporarily as a nest, that is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…Nest sites in the present study did not differ significantly from controls in aspects of their microhabitat, including canopy, ground, and/or water cover and surrounding tree size and density (i.e., considering all trees within a 10 × 10 m plot), characteristics that were predicted to provide protection from the elements and/or predators, either by shielding nests from rain and/or concealing nests against aerial predators (high % canopy cover), or by allowing the detection (low % ground cover) and avoidance of terrestrial predators (high tree density or size) by increasing visibility and providing multiple escape routes. These results corroborate earlier studies that have found the thermoregulatory and antipredator benefits of nest use to be secondary (birds: Heenan & Seymour, ; primates: Hediger, ; Kappeler, ) or unimportant to nesting decisions (Heenan & Seymour, ; Tomás et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Nest sites in the present study did not differ significantly from controls in aspects of their microhabitat, including canopy, ground, and/or water cover and surrounding tree size and density (i.e., considering all trees within a 10 × 10 m plot), characteristics that were predicted to provide protection from the elements and/or predators, either by shielding nests from rain and/or concealing nests against aerial predators (high % canopy cover), or by allowing the detection (low % ground cover) and avoidance of terrestrial predators (high tree density or size) by increasing visibility and providing multiple escape routes. These results corroborate earlier studies that have found the thermoregulatory and antipredator benefits of nest use to be secondary (birds: Heenan & Seymour, ; primates: Hediger, ; Kappeler, ) or unimportant to nesting decisions (Heenan & Seymour, ; Tomás et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…I consider this to be emerging evidence that habitual nesting sites (such as those described by Kortlandt [1983], Goodall [1986], and Baldwin, et al [1982]) are likely part of the learned landscape, along with other localized resources such as nut trees, seasonal fruiting patches and good termite mounds. Yet most authors would still be reluctant to equate a ''nest site'' with a ''home'' [Hediger, 1977]. If we want to understand the evolution of these different patterns, we need to focus on better defining the elements of similarity and difference and evaluating the types of evidence to search for that could elucidate prehistoric patterns of nesting behaviors.…”
Section: Comparative Behavioral Context Of Nesting Behaviormentioning
confidence: 99%
“…He used the term "nest," which had been popularized during 19th century African expeditions [Du Chaillu, 1861]. The pop-ularity of the term "nest" has been lamented by several authors [Baldwin et al, 1981;Groves & Sabater Pi, 1985;Hansell, 1984Hansell, , 2005Hediger, 1977;Mc-Grew, 1992; Thorén et al, 2010] because while great ape nests appear similar to large bird nests, the resemblance is superficial. A bird (and even strepsirhine [Kappeler, 1998]) nest is a fixed point that serves as cache for resources and as a central base during foraging.…”
Section: Introductionmentioning
confidence: 99%